Implementasi Kebijakan Pemerintah Tentang Prioritas Penggunaan Dana Desa di Desa Talaga Paca Dan Wangongira, Kabupaten Halmahera Utara - richard djiko; Bagus Subardi (Department of Public Administration, Muhammadiyah University of Makassar, 2020)
This study aims to determine how the implementation of government policies regarding the priority of the use of village funds for community empowerment and village development activities in the villages of Telaga Paca and Wangongira, North Halmahera district. This study use descriptive qualitative approach. Source of data used in this study uses primary and secondary data. And the results of the study can be concluded that what is mandated by the law is not in line with what is the reality in the field, whether it is development activities and community empowerment, because the village has village autonomy so that each village has the right to regulate and manage its own household according to the needs of the village